Konsep Ta’dib Menurut Naquib Al-Attas dalam Pendidikan Islam - Hidayat, Muhtar; Mulyanto, Mulyanto (Lembaga Yasin AlSys, 2024)
This article discusses the concept introduced by Syed Muhammad Naquib Al-Attas. His thoughts are considered fundamental because his concept differs from commonly used terms in Islamic education. Al-Attas proposes the concept of ta'dib as a replacement for the terms tarbiyah and ta'lim, which he considers less appropriate in the context of Islamic education. This article aims to delve deeper into the concept of ta'dib proposed by Al-Attas, elaborate on the meaning of the concept, and evaluate whether it is true that the concepts of tarbiyah and ta'lim are less appropriate in Islamic education. This research is literature-based, using a qualitative approach that produces descriptive data in the form of written texts. The main focus of this study is on Muhammad Naquib Al-Attas's thoughts on the concept of ta'dib. Primary data is obtained from Al-Attas's books and scholarly journals discussing his thoughts. Secondary and supporting data are collected from books, the internet, and other sources relevant to this study. The conclusion of this article is that Al-Attas considers the most appropriate concept for Islamic education to be ta'dib, not tarbiyah. According to him, the most fundamental problem in current Islamic education is the loss of adab (manners). The concept of ta'dib, if applied comprehensively, integrally, and systematically in the practice of Islamic education, is expected to overcome various challenges in the development of Muslim human resources and produce a generation with manners through education with the concept of ta'dib.